Two-layer model predictive control of systems with independent dynamics and shared control resources. Issue 3 (2019) - Bella, Alessio La; Bonassi, Fabio; Farina, Marcello; Scattolini, Riccardo
Abstract: This paper describes an approach to the design of a controller for a system made by dynamically decoupled subsystems. Each subsystem is endowed with local actuators that, in normal operating conditions, are able to compensate for disturbances and to provide the required control action. If, due to too large disturbances, the local control action is not sufficient, the actuators of the neighbouring subsystems can provide the required control contribution. The control scheme is designed according to a hierarchical approach: at the lower layer local Model Predictive Controllers (MPC) are used to compute the required control action. The information about any shortage or excess of control is sent to a supervisor that, if needed, re-balances the local control actions to guarantee global disturbance rejection properties. A simulation example concerning the coordination of small electrical grids is discussed to show the performances of the proposed solution.